School-Based Violent Victimization in Turkey: Are Correlates Gender-Specific?. Issue 9 (May 2021) - Deryol, Rustu; Wilcox, Pamela; Dolu, Osman
The present study builds upon limited recent work suggesting that the correlates of adolescent school-based victimization are gendered in important ways. In particular, it broadens the international scope of such research by exploring the potentially gendered nature of predictors of school-based violent victimization in Turkey. Like much of the previous U.S.-based research, the focus here is on the potentially gender-specific effects of variables derived from lifestyle-routine activities and low self-control theories. For this article, the data are based on a subsample from The National High School Offending and Victimization Survey in Turkey. The subsample included 461 male and 452 female students from 15 high schools within Turkey's Mersin province. Binary regression coefficients were estimated for 20 datasets generated through a multivariate sequential imputation technique, with results then pooled. Binary logistic regression models showed that many of the propositions of lifestyle-routine activities theory were generally supported for both genders. However, some results were suggestive of the notion of "gendered opportunity"—that indicators of opportunity for victimization vary across males and females. Gender-specific findings imply that there are some important differences in terms of the impact of low self-control and lifestyle, which might require gender-specific interventions. In addition, regardless of gender, students who reported that school administration was effective in controlling weapons at school were less likely to be victimized, and students who reported there being unsupervised areas at their schools had higher odds of victimization. As such, supervisory practices and target hardening strategies seem important for curbing all students' victimization risk in Turkey.